Dexmedetomidine – Commonly Used in Functional Imaging Studies – Increases Susceptibility to Seizures in Rats But Not in Wild Type Mice - Bortel, Aleksandra; Pilgram, Roland; Yao, Ze Shan; Shmuel, Amir (Frontiers in Neuroscience, 2020)
Functional MRI of the resting-state utilizes spontaneous fluctuations in metabolic and hemodynamic signals to indirectly infer the underlying local changes in neuronal activity. For correct interpretation of spontaneous fluctuations and FC in the resting-state, it is important to characterize the neuronal mechanisms of fMRI in animal models. Animal studies of the evoked response and resting-state commonly use dexmedetomidine sedation. It has been demonstrated that dexmedetomidine combined with potent sensory stimuli are prone to induce seizures in Sprague-Dawley rats. To characterize these seizures, here we combined optical imaging of intrinsic signals and cerebral blood flow with neurophysiological recordings. We characterize the susceptibility to seizures as a function of time from the beginning of dexmedetomidine administration. We show that these seizures are associated with spatially extensive high-amplitude cerebral blood flow and blood oxygenation, prone to be misinterpreted as normal responses in functional imaging studies that do not use neurophysiological recordings. Lastly, we demonstrated that no seizures are generated in C57 mice similarly sedated with dexmedetomidine and stimulated with similar potent stimuli. We conclude that caution should be practiced in experiments that combine the administration of potent stimuli with dexmedetomidine sedation, because high-amplitude hemodynamic responses evoked by peripheral stimulations are possibly due to the induction of epileptic activity in the cortical brain area. We further conclude that the susceptibility to dexmedetomidine-induced seizures is species dependent.